Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Dañobeitia, Juan Jose; Pouliquen, Sylvie; Johannessen, Truls; Basset, Alberto; Cannat, Mathilde; Pfeil, Benjamin Gerrit; Fredella, Maria Incoronata; Materia, Paola; Gourcuff, Claire; Magnifico, Giuseppe; Delory, Eric; del Rio Fernandez, Joaquin; et al. (Frontiers in Marine Science, 2020)
Research Infrastructures (RIs) are large-scale facilities encompassing instruments, resources, data and services used by the scientific community to conduct high-level research in their respective fields. The development and integration of marine environmental RIs as European Research Vessel Operators [ERVO] (2020) is the response of the European Commission (EC) to global marine challenges through research, technological development and innovation. These infrastructures (EMSO ERIC, Euro-Argo ERIC, ICOS-ERIC Marine, LifeWatch ERIC, and EMBRC-ERIC) include specialized vessels, fixed-point monitoring systems, Lagrangian floats, test facilities, genomics observatories, bio-sensing, and Virtual Research Environments (VREs), among others. Marine ecosystems are vital for life on Earth. Global climate change is progressing rapidly, and geo-hazards, such as earthquakes, volcanic eruptions, and tsunamis, cause large losses of human life and have massive worldwide socio-economic impacts. Enhancing our marine environmental monitoring and prediction capabilities will increase our ability to respond adequately to major challenges and efficiently. Collaboration among European marine RIs aligns with and has contributed to the OceanObs’19 Conference statement and the objectives of the UN Decade of Ocean Science for Sustainable Development (2021–2030). This collaboration actively participates and supports concrete actions to increase the quality and quantity of more integrated and sustained observations in the ocean worldwide. From an innovation perspective, the next decade will increasingly count on marine RIs to support the development of new technologies and their validation in the field, increasing market uptake and produce a shift in observing capabilities and strategies.